2018
DOI: 10.1111/pedi.12637
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of physical fitness to individual and ethnic differences in risk markers for type 2 diabetes in children: The Child Heart and Health Study in England (CHASE)

Abstract: BackgroundThe relationship between physical fitness and risk markers for type 2 diabetes (T2D) in children and the contribution to ethnic differences in these risk markers have been little studied. We examined associations between physical fitness and early risk markers for T2D and cardiovascular disease in 9‐ to 10‐year‐old UK children.MethodsCross‐sectional study of 1445 9‐ to 10‐year‐old UK children of South Asian, black African‐Caribbean and white European origin. A fasting blood sample was used for measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…We found that NETCRF at age 46 was associated with blood pressure and blood‐borne cardiometabolic risk factors at age 46 after adjustment for NETCRF at age 10. Studies of children of different ethnic groups suggest that it is plausible that genes explain at least some of the association between fitness and health in childhood . Studies of adults suggest that it is plausible that habitual physical activity explains at least some of the association between fitness and health in adulthood …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that NETCRF at age 46 was associated with blood pressure and blood‐borne cardiometabolic risk factors at age 46 after adjustment for NETCRF at age 10. Studies of children of different ethnic groups suggest that it is plausible that genes explain at least some of the association between fitness and health in childhood . Studies of adults suggest that it is plausible that habitual physical activity explains at least some of the association between fitness and health in adulthood …”
Section: Discussionmentioning
confidence: 99%
“…Studies of children of different ethnic groups suggest that it is plausible that genes explain at least some of the association between fitness and health in childhood. 17 Studies of adults suggest that it is plausible that habitual physical activity explains at least some of the association between fitness and health in adulthood. 1 The present study is one of the largest studies with data across the life course to examine the associations between estimated cardiorespiratory fitness in childhood and cardiometabolic risk factors in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple risk factors for the diseases for which we found significant F ROH associations that differ between British South Asians and White British people (e.g., diet and lifestyle factors for T2D, 44 , 45 , 46 , 47 , 48 , 49 socioeconomic status and experience of racial discrimination for PTSD 50 , 51 ). However, there are several reasons we feel these are unlikely to confound our results here.…”
Section: Discussionmentioning
confidence: 63%
“…In its scientific statement on atherosclerotic cardiovascular diseases in SAs in the United States, 3 the American Heart Association recommends that physicians demonstrate "cultural competency in understanding the increased risk of atherosclerotic cardiovascular disease in SA patients and provide SA-specific recommendations on medications, diet, and lifestyle modifications." 3 As evidence shows that risk factors for these conditions have origins in childhood 23,27 and problematic diet and lifestyle practices in childhood can have life-long consequences, [12][13][14][15][16][17][18][19] pediatricians can play a very important role in this effort by counseling SA families effectively on prevention strategies starting in childhood. This study highlights several health challenges noted by pediatricians in SA children, especially problematic feeding practices and their consequences and significant barriers to addressing these challenges.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] Parent-led and pressurizing feeding or force-feeding have been associated with obesity and other problems. [16][17][18][19] Force-feeding, prolonged parent-led feeding, calorie-dense diets, [20][21][22] and lower levels of physical activity 23 have been reported in SA diaspora. Although only a few studies have explored these issues in the United States, they report similar practices.…”
Section: Introductionmentioning
confidence: 99%